Digital Sign Language Applications: Enhancing Inclusive Communication for the Deaf Community - Swastikawara, Sinta (Department of Special Education, 2025)
Advances in digital technology have brought about various sign language learning applications as innovative solutions to bridge communication barriers between the deaf community and the hearing community. This study aims to analyze the role of sign language learning applications in improving inclusive communication and to examine the perceptions of both groups regarding the use of this technology. This study uses a qualitative approach with an intrinsic case study method. The research subjects consist of six individuals, including three members of the Deaf community and three hearing users of the application in Malang City. Data collection techniques were conducted through in-depth interviews, while data analysis used the interactive model of Miles and Huberman. The results of the study indicate that digital applications facilitate initial access to sign language learning and play a role in reducing communication anxiety for the hearing community. However, the involvement of the Deaf community in the development of the application remains limited, thus failing to fully represent the needs and communication culture of the Deaf community.